Human chorionic villous mesenchymal stem/stromal cells modify the effects of oxidative stress on endothelial cell functions. (November 2017) - Abumaree, M.H.; Hakami, M.; Abomaray, F.M.; Alshabibi, M.A.; Kalionis, B.; Al Jumah, M.A.; AlAskar, A.S.
Abstract: Mesenchymal stem/stromal cells derived from chorionic villi of human term placentae (pMSCs) produce a unique combination of molecules, which modulate important cellular functions of their target cells while concurrently suppressing their immune responses. These properties make MSCs advantageous candidates for cell-based therapy. Our first aim was to examine the effect of high levels of oxidative stress on pMSC functions. pMSCs were exposed to hydrogen peroxide (H2 O2 ) and their ability to proliferate and adhere to an endothelial cell monolayer was determined. Oxidatively stressed pMSCs maintained their proliferation and adhesion potentials. The second aim was to measure the ability of pMSCs to prevent oxidative stress-related damage to endothelial cells. Endothelial cells were exposed to H2 O2, then co-cultured with pMSCs, and the effect on endothelial cell adhesion, proliferation and migration was determined. pMSCs were able to reverse the damaging effects of oxidative stress on the proliferation and migration but not on the adhesion of endothelial cells. These data indicate that pMSCs are not only inherently resistant to oxidative stress, but also protect endothelial cell functions from oxidative stress-associated damage. Therefore, pMSCs could be used as a therapeutic tool in inflammatory diseases by reducing the effects of oxidative stress on endothelial cells. Highlights: Mesenchymal stem/stromal cells derived from chorionic villi of human term placentae (pMSCs) produce a unique combination of molecules that make them a suitable candidate for cell-based therapy. Oxidatively stressed pMSCs can maintain their proliferation and adhesion potentials. pMSCs are able to reverse the damaging effects of oxidative stress on endothelial cell proliferation and migration. pMSCs are resistant to oxidative stress, and can protect endothelial cell functions from oxidative stress-associated damage. pMSCs could be used as a therapeutic tool in inflammatory diseases by reducing the effects of oxidative stress on endothelial cells.